Redox- and pH-responsive emulsions based on TiO2 nanoparticles and ferrocene derivates. (5th September 2022) - Ge, Shujin; Zhang, Shang; Chang, Xiujie; Li, Aixiang; Wang, Weiwei; Li, Qiuhong; Wang, Zhaodong
Abstract : The stabilization of emulsion depends on the combination adsorption of surfactant-modified nanoparticles and surfactants on the oil-water interface. Abstract : We synthesized a novel surfactant, ferrocene azine (FcA), and developed a redox- and pH-responsive emulsion stabilized by TiO2 nanoparticles and oxidized ferrocene azine (Fc + A) with fluorescence through simple mixing instead of complex modification steps, where both Fc + A and TiO2 nanoparticles modified in situ by Fc + A adsorbed at the oil–water interface to synergistically stabilize emulsions. Based on the redox activity of ferrocenyl, the stability of the emulsion could be modulated. Moreover, the pH responsiveness of the emulsion was also endowed utilizing the generally ignored pH-controlled surface charge inversion of nanoparticles. This study proposes a synergistic stabilization interaction between surfactants and surfactant-modified nanoparticles with very low concentrations, which provides a new understanding for the stabilization mechanism of emulsions.